O filme animado: trajetória histórica, storyboard e design de personagens - Gomes, Vítor Hugo Vila Nova [UNESP] (2016)
Animation is a versatile art full of possibilities. Even though it is relatively new, its history is remarkable, with many contribution e technological innovations in little more than a century. An excellent medium for telling stories, animation uses storyboards and characters to bring the narrative to life and guarantee an adequate communication with the viewer. Through a bibliographic survey, this paper presents the development of animation in different parts of the world from the last years of the XIX century until the present days, as well as the fundamentals of character design e storyboard technique